Pengaruh Desain Aerodinamika Terhadap Efisiensi Bahan Bakar pada Kendaraan Bermotor Listrik - Raka Pratama (Journal of Engineering and Technological Science, 2025)
The aerodynamic design of electric vehicles (EVs) significantly influences their overall energy efficiency, particularly in reducing air drag and improving battery range. This study aims to analyze the effect of aerodynamic body design on the energy consumption of electric motor vehicles using computational fluid dynamics (CFD) simulations. Three different vehicle models with varying drag coefficients (Cd = 0.22, 0.28, and 0.35) were evaluated under identical speed and wind tunnel conditions. The results indicate that reducing the drag coefficient by 0.1 can increase the vehicle’s travel range by approximately 8–12%, depending on speed and battery capacity. Streamlined body shapes and underbody smoothing were found to be the most effective design features in minimizing drag. This study highlights the critical role of aerodynamic optimization in improving the sustainability and performance of electric vehicles, offering design guidelines for future EV development.